2016
DOI: 10.1515/spircare-2016-0126
|View full text |Cite
|
Sign up to set email alerts
|

Ausdrucksformen der Spiritualität bei Schülern und jungen Erwachsenen

Abstract: The latter has no decided religious connotation and may thus be of relevance also for a-religious persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Furthermore, items the Freiburg group had benefited from using were added. Three scales by Büssing, appropriate for analyses in more secular culture (ASP [73,74] and SpREUK-15 [75,76]) were proposed as additional modules for future research. More items that were identified during the NGT-process as thematically related were grouped in leading to fewer overall questionnaire batteries (see Section 2.4 below).…”
Section: Expert Roundmentioning
confidence: 99%
“…Furthermore, items the Freiburg group had benefited from using were added. Three scales by Büssing, appropriate for analyses in more secular culture (ASP [73,74] and SpREUK-15 [75,76]) were proposed as additional modules for future research. More items that were identified during the NGT-process as thematically related were grouped in leading to fewer overall questionnaire batteries (see Section 2.4 below).…”
Section: Expert Roundmentioning
confidence: 99%
“…In einer Untersuchung zu den Ausdrucksformen der Spiritualität bei 2.468 jungen Erwachsenen (Altersmittel 18 ± 2 Jahre), von denen sich 73 % als nicht-religiös bezeichnen würden (Büssing et al 2016), konnte bestätigt werden, dass religiös geprägte Aspekte von Spiritualität bei ihnen von geringem Interesse waren; Transzendenz-Überzeugungen waren etwas stärker ausgeprägt (moderater Ausprägungsbereich), eine existenzialistische Suche nach Weisheit/Einsicht deutlich stärker und ein bewusster Umgang mit anderen/Mitgefühl von größter Bedeutung. In diesen Untersuchungen hatten jungen Männer signifikant geringere Ausprägungs-Scores als junge Frauen (Büssing et al 2016).…”
Section: Einführungunclassified
“…To cover a wide variety of important aspects of spirituality beyond conceptual boundaries, we have performed an expert survey among 38 individuals from different religious and non-religious affiliations (i.e., Catholics, Protestants, members of the Anthroposophic "Christengemeinschaft", Bahá´í, Muslims, Jews, Buddhists, and atheists), and asked for their individual view of spirituality and its individual expression in their lives [15]. These statements revealed that the individual concepts of spirituality depend on the contextual world-view and refer to an immaterial, not sensual comprehensible truth (God, "presence", "powers"), which nevertheless might be experienced and can be an orientation in life [15].…”
Section: Development Of the Aspects Of Spirituality (Asp) Questionnairementioning
confidence: 99%
“…These statements revealed that the individual concepts of spirituality depend on the contextual world-view and refer to an immaterial, not sensual comprehensible truth (God, "presence", "powers"), which nevertheless might be experienced and can be an orientation in life [15].…”
Section: Development Of the Aspects Of Spirituality (Asp) Questionnairementioning
confidence: 99%
See 1 more Smart Citation